Slowing deforestation in Indonesia follows declining oil palm expansion and lower oil prices - Gaveau, D.L.A.; Locatelli, Bruno; Salim, M.A.; Husnayaen, H.; Manurung, T.; Descals, A.; Angelsen, A.; Meijaard, E.; Sheil, D. (Research Square Platform LLC, 2021)
Much concern about tropical deforestation focuses on oil palm plantations, but their impacts remain poorly quantified. Using satellites, we estimated annual expansion of large-scale (industrial) and smallholder oil palm plantations and their overlap with forest loss from 2001 to 2019 in Indonesia, the world’s largest palm oil producer. Over nineteen years, the area under oil palm doubled, reaching 16.24 million hectares (Mha) in 2019 (64% industrial; 36% smallholder), more than official estimates of 14.72 Mha. This expansion was responsible for nearly one-third (2.85 Mha) of Indonesia’s loss of old-growth forests (9.79 Mha). Industrial plantations were associated with three times as much forest conversion as smallholder plantings (2.13 Mha vs 0.72 Mha). New plantations peaked in 2009 and 2012 and declined thereafter. Deforestation peaked in 2016 and fell below pre-2004 levels in 2017-2019. Expansion of industrial plantations and forest loss were correlated with palm oil prices. A price decline of 1% was associated with a 1.08% decrease in new industrial plantations and with a 0.68% decrease of forest loss. This slow-down provides an opportunity for the Indonesian government to focus on details of sustainable oil palm management. If prices rise, effective regulations will remain key to minimising deforestation.